The Influence of Short Wavelength Laser on the Pupae Development of the Old World Screw- Worm Fly (OWSWF) Chrysomya bezziana Villeneuve (Diptera: Calliphoridae) - Al-Ani, Rana R.; Jawad, Hussain A.; Al-Izzi, Muhammed A. J. (Iraqi Journal of Laser, 2003)
The biological effects of pulsed N2-laser on the old world screw-worm fly, Chrysomya bezziana Villeneuve in the pupal stage were investigated. Different laser parameters were involved in this work. The old pupae of 1, 2, 3, 4 and 5 days were exposed to laser radiation during 10, 30 and 60 second with repetition rate 10, 20 and 30 pulse/second. The percent of normal adults emergence (female and male) was investigated. The results showed that the adults emergence was highly decreased as the repetition rate and exposure time increased when the pupae irradiated for 1, 2 and 3 days old as compared with 4 and 5 days. The results also indicated that the pupal period was significantly increased of irradiated pupae for 1, 2, 3 and 4 days old, while the 5 days old pupa was decreased.